Vita sexualis zen s hyperfenylalaninémií - Dolezal, A; St'astná, S; Hyánek, J; Zivný, J (Ceska gynekologie, 2002)
OBJECTIVE: Characteristics of sexual life in women with hyperphenylalaninemia. DESIGN: Anamnestic study. SETTING: Department of Obstetrics and Gynaecology and Institute of Inherited Metabolic Disorders of General Faculty Hospital and 1st Medical Faculty of Charles University in Prague, Department of Clinical Biochemistry, Haemathology and Immunology of Hospital Na Homolce in Prague. METHODS: Characteristics of sexual life were studied in a group of 16 women with hyperphenylalaninemia. RESULTS: One fourth of the women lives without sex. In the rest of them sexual function is normal. CONCLUSION: One fourth of the women stays out of reproduction.
Keywords: fenylketonurie; Female; Humans; Phenylketonurias; sexuální chování; Adolescent; ženské pohlaví; dospělí; lidé; Coitus; Adult; Sexual Behavior; koitus; mladiství